2015
DOI: 10.3892/ijmm.2015.2156
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophil peptides induce interleukin-8 in intestinal epithelial cells through the P2 receptor and ERK1/2 signaling pathways

Abstract: Human neutrophil peptides (HNPs) are antimicrobial peptides produced predominantly by neutrophils. We have previously reported that HNP 1-3 levels are increased in the sera and plasma of patients with active ulcerative colitis. The increased expression of interleukin-8 (IL-8) has also been demonstrated in the colonic mucosa of patients with active ulcerative colitis. HNPs induce IL-8 in lung epithelial cells and monocytes through the P2Y6 signaling pathway. However, the association between HNPs and IL-8 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The vessels’ attraction was confirmed also by HE at the end of in ovo incubation (Figure c). In addition, it is reported that the stimulation of tumor cell lines with DEFA3 resulted in the induction of IL‐8 overexpression (Ibusuki et al, ; Khine et al, ). Also in our hands, stimulation of HT‐29 cell line with exogenous DEFA3 (Figure d) or conditioned media obtained through DN and DT matrices disaggregation (Figure e) induced the overexpression of IL‐8 in respect to the untreated cells (Figures d and e), with no significant difference between DN and DT conditioned cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vessels’ attraction was confirmed also by HE at the end of in ovo incubation (Figure c). In addition, it is reported that the stimulation of tumor cell lines with DEFA3 resulted in the induction of IL‐8 overexpression (Ibusuki et al, ; Khine et al, ). Also in our hands, stimulation of HT‐29 cell line with exogenous DEFA3 (Figure d) or conditioned media obtained through DN and DT matrices disaggregation (Figure e) induced the overexpression of IL‐8 in respect to the untreated cells (Figures d and e), with no significant difference between DN and DT conditioned cells.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, it has been shown that the release of neutrophils proteins into the inflamed tumor stroma is a strong activator of chemokine CXCL‐8, also known as IL‐8, in resident cells (Khine et al, ). In addition, a recent research work showed that released DEFA proteins are able to induce the secretion of IL‐8 in HT‐29 cell line through the activation of ERK1/2 signaling pathway (Ibusuki et al, ). Also in our hand, HT‐29 cells were able to over‐expressed IL‐8 transcript after conditioning with either exogenous or decellularized matrix‐related DEFA3, but this increase in gene expression was statistically different between acellular tumor and healthy mucosa samples only when the cell line was cultivated in 3D biologic‐derived environment.…”
Section: Discussionmentioning
confidence: 99%
“…This is also likely because the ectonucleotidase NTPDase1 (CD39) has been shown to control IL-8 release in human PMNs (108). P2Y6R could also play a role because IL-8 release in epithelial cells induced by neutrophil defensins is blocked by MRS2578 (109). MRS2578 could also switch off NETosis in human PMNs, only to shorten their lifespan and accelerate apoptosis (72).…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of HNP-1 reduce the proliferation and viability of intestinal epithelial cells (14). Additionally, HNP-1 induces IL-8 production from intestinal epithelial cells in a dose-dependent manner, which may stimulate additional neutrophil accumulation in the intestine (36). …”
Section: Discussionmentioning
confidence: 99%